2005
DOI: 10.1002/ijc.21020
|View full text |Cite
|
Sign up to set email alerts
|

hTERT gene copy number is not associated with hTERT RNA expression or telomerase activity in colorectal cancer

Abstract: In a majority of malignant human tumors telomerase activity can be detected, suggesting an immortal phenotype. Expression of the reverse transcriptase subunit, hTERT, in the human telomerase complex is required for telomerase activity. The regulation of hTERT, from gene level to a fully functional protein, is still a poorly understood process. Increased copy number of the hTERT gene has been demonstrated in a significant portion of established cell lines and tumors of different origin but its relevance for tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Insufficient hTR up-regulation could be one of the explanations for the previously observed nonassociation between hTERT amplification and telomerase activity in some tumors (10)(11)(12)(13). Our study is the first to examine the expression of other telomerase components, hTR and dyskerin, in the context of hTERT-immortalized HMECs, and provides further direct evidence that hTR is limiting for telomerase activity and telomere length maintenance.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Insufficient hTR up-regulation could be one of the explanations for the previously observed nonassociation between hTERT amplification and telomerase activity in some tumors (10)(11)(12)(13). Our study is the first to examine the expression of other telomerase components, hTR and dyskerin, in the context of hTERT-immortalized HMECs, and provides further direct evidence that hTR is limiting for telomerase activity and telomere length maintenance.…”
Section: Discussionsupporting
confidence: 51%
“…9). Amplification of the hTERT gene has been observed in various human cancer cell lines and tumors, and is also thought to be a mechanism of telomerase activation (10)(11)(12)(13).…”
Section: In Ref 7)mentioning
confidence: 99%
“…31 In the present study, the Trapeze XL Telomerase detection kit (Chemicon International, Temecula, CA) was used to analyze CHAPS extracts from the A498 cell line at 0.5 lg protein of extract/assay. Band intensities were quantified using phosphorimager and Image-Quant software (Molecular Dynamics, Sunnyvale, CA) and the telomerase activity was expressed as total product generated (TPG).…”
Section: Telomerase Activity Determinationmentioning
confidence: 99%
“…In the current study, it was found that hTERT mRNA expressions were higher in tumour tissues than in the normal tissues of almost half of the patients. Palmqvist et al (15) determined a positive telomerase activity in 77%, and varied levels of hTERT mRNA expressions in 91% of cases in their study conducted with colorectal cancer patients. In another study, hTERT expressions were observed in all tumour samples from colorectal cancer patients and found to be significantly higher than those in normal tissues (16).…”
Section: Discussionmentioning
confidence: 99%